Primate brain-specific cytoplasmic transcript of the Alu repeat family. - Watson, J B (1987)
A 200-nucleotide RNA homologous to the left monomer of Alu elements was expressed in monkey and human brain and in cell lines but not in nonneural monkey tissues. Similar brain-specific transcription of identifier sequences was observed in rats. Thus, expression of selected repetitive DNA families is a conserved process in mammalian brain.